Pengaruh Workload, Work-Family Conflict, Job Satisfaction, Organizational Commitment terhadap Turnover Intention Guru SMA Swasta: The Influence of Workload, Work-Family Conflict, Job Satisfaction, and Organizational Commitment on Turnover Intention among Private High School Teachers - Margareta Rina Asriastuti; Ardi Kho (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
Teacher turnover intention poses a serious threat to teacher retention and the sustainability of national educational quality, particularly in private high schools, where high workloads often coincide with limited compensation. A preliminary survey of 15 private high school teachers in Tangerang Regency revealed that 73.3% of respondents frequently considered leaving the profession or changing schools. This study simultaneously examines the effects of workload, work-family conflict, job satisfaction, and organizational commitment on teacher turnover intention within a single model. This area has received limited research attention in the context of private high school teachers in Indonesia. An explanatory quantitative approach using a cross-sectional survey design was applied to 100 private high school teachers in Tangerang Regency, selected through purposive and snowball sampling. Data were collected via a five-point Likert scale questionnaire and analyzed using PLS-SEM (SmartPLS 4), grounded in the Job Demands-Resources and Conservation of Resources frameworks. Six of the ten hypotheses were supported. Workload was found to have a positive effect on turnover intention and work-family conflict, and a negative effect on job satisfaction. Work-family conflict negatively affected job satisfaction; job satisfaction positively affected organizational commitment; and organizational commitment negatively affected turnover intention. The effect of workload on organizational commitment was significant but positive in direction; thus, the hypothesis regarding this relationship was not supported. Teacher turnover intention is primarily driven directly by workload, while organizational commitment serves as the strongest protective factor. Managing workload and strengthening organizational commitment are key priorities for teacher retention policies in schools.